Social Media Effectiveness in Increasing Richeese Factory Product Sales in Bengkulu - Azuwandri; Gustini (CV. Era Digital Nusantara, 2026)
This study examines how social media is managed by Richeese Factory and evaluates its role in increasing product sales among consumers in Bengkulu. A quantitative explanatory design was used. Data were collected through a five-point Likert-scale questionnaire administered to 100 Richeese Factory consumers selected through accidental sampling. The instrument was assessed through validity and reliability tests, while the data were analysed using normality, heteroscedasticity, multicollinearity, and multiple linear regression tests with SPSS 20. All questionnaire items were valid, and the three constructs were reliable, with Cronbach’s alpha values ranging from 0.638 to 0.757. The residuals were normally distributed, and no heteroscedasticity or multicollinearity was identified. Regression results show that practical social media use had a positive and significant effect on increased product sales (B = 0.320; β = 0.507; p < 0.001), whereas perceived media effectiveness had a positive but statistically non-significant effect after the social media variable was controlled (B = 0.141; p = 0.206). Instagram and TikTok promotions, price discounts, bundled offers, and online ordering facilities were the principal practices supporting consumer awareness and purchase decisions. The findings underline the importance of consistent, interactive, and measurable social media management in strengthening fast-food sales performance.